Ecologia e Comportamento da Formiga-Gigante Dinoponera gigantea (lnsecta: Hymenoptera: Formicidae): Estudos no Campo e laboratório - (:unkn) unknown (Museu Paraense Emílio Goeldi, 2006)
The tapiaí ant (Dinoponera gigantea Perty, 1833), L inhabiting the terra firme forests and shrublands of the Amazon, is the largest ant in the Neotropics, reaching up to 3 in. The ants show no polymorphism and workers lay eggs under special conditions. This work aims to determine how work is organized in natural and artificial colonies. Colonies from Benevides, Pará, were kept in the laboratory at the Goeldi Museum, allowing the marking of individuals and the monitoring of their behavior. Food items accepted by the ants included dead and live insects and arachnids, boiled egg and raw beef. There was cannibalism in some colonies when larvae, pupae and adult ants were consumed. Recognition between individuals from the same colony was noted, but individuals from distant nests often exhibited no aggression toward each other. In captivity, there was no food exchange between adults, but larvae received food from several adult ants. The excavated colonies contained between 30 and 80 adult ants. Foraging was always an individual act, with no evidence of recruitment of other ants, but one individual, when stimulated with the offer of prey, returned to the same spot, which was 3 m away from the nest, up to 23 times. Dissection of more than 50 ants collected in the field outside nests found no egg-bearing queen, which must have claustral habits. When live larvae from the colony were offered, these were soon accepted by foraging ants, but it is not known whether they were reintegrated into the colony or consumed in the nest. Larvae from other colonies were less accepted, as were pupae from strange colonies. Thus, it is concluded that there is recognition of immatures from the colony, even outside the nest. The immature forms in a nest could serve as a food reserve in case of colony starvation.
Ecology and Behavior of the Giant Ant Dinoponera gigantea (Insecta: Hymenoptera: Formicidae): Field and Laboratory Studies
Keywords: Dinoponera gigantea; lnsecta; Hymenoptera; Formicidae; CNPQ::CIENCIAS BIOLOGICAS::ZOOLOGIA::COMPORTAMENTO ANIMAL